Plasmid role in agar utilization by Pseudomonas sp. HK1 (Baghdad Science Journal, 2007)
Forty different samples (water and soil) were collected from different places in Iraq and Syria. Only (6) isolates showed the ability to grow and utilize agar as a sole source of carbon and energy. Morphological, cultural characterization and biochemical tests confirmed that These isolates belonging to genus Pseudomonas (HK1-HK6) .Plasmid profiles results showed that these isolates were harbored (2 -3) small Plasmids . HK1 isolate was selected because of its efficiency and ability to grow in high density on agar media for transformation and curing experiments, these were checked by transformation experiments after their expression in E. coli MM294. The genes responsible for agar utilization were located on these plasmids . These results were confirmed by data obtained from curing experiments.